The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1063/1.5025545
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian nonparametric approach to dynamical noise reduction

Abstract: We propose a Bayesian nonparametric approach for the noise reduction of a given chaotic time series contaminated by dynamical noise, based on Markov Chain Monte Carlo methods. The underlying unknown noise process (possibly) exhibits heavy tailed behavior. We introduce the Dynamic Noise Reduction Replicator model with which we reconstruct the unknown dynamic equations and in parallel we replicate the dynamics under reduced noise level dynamical perturbations. The dynamic noise reduction procedure is demonstrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The case of an impulsive noise process: Here we mostly elaborate on the efficiency of the proposed SM-GSBR model. We generate a short time-series x + 1:n of length n = 500, via the Dual-Hénon map in (19), yet influenced by the additive impulsive stochastic component…”
Section: The Dual-hénon Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…The case of an impulsive noise process: Here we mostly elaborate on the efficiency of the proposed SM-GSBR model. We generate a short time-series x + 1:n of length n = 500, via the Dual-Hénon map in (19), yet influenced by the additive impulsive stochastic component…”
Section: The Dual-hénon Mapmentioning
confidence: 99%
“…Namely, the procedures of the system identification and of the stochastic approximation are performed in parallel, in a similar fashion as the Dynamic Noise Reduction Replicator model described in Ref. [19]. Our method is parsimonious, due to its flexibility induced by the general functional form of the deterministic part, and the application of a GSB mixture process prior over the additive stochastic component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach for continuous time-series modeling based on time dependent Geometric Stick-Breaking process mixtures can be found in Mena, Ruggiero, and Walker (2011). For a Bayesian nonparametric nonlinear noise reduction approach see Kaloudis and Hatjispyros (2018).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, in this thesis we have applied Bayesian nonparametric methods in the problems of reconstruction, prediction [MKH17], noise reduction [KH18] and approximation of the stable manifold [HK19]. In all of the above problems we have shown that models based on the GSB random probability measures are efficient, with lower mean execution times and and at the same time are easier to implement than the corresponding Dirichlet Process based models.…”
Section: Discussionmentioning
confidence: 99%